2018
DOI: 10.1037/cep0000126
|View full text |Cite
|
Sign up to set email alerts
|

Are lexical factors immune to response modality in backward recall? The effects of imageability and word frequency.

Abstract: In immediate serial recall, it is well established that performance is influenced by lexical factors such as imageability and word frequency. However, when participants are asked to recall the to-be-remembered items in their reverse order, known as backward recall, lexical factors produced contradictory findings. In 4 experiments, we tested the role of response modality in modulating the effects of imageability and word frequency in backward recall. The magnitude of the 2 tested lexical factors was only slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…An additional concern is that response modality may be a factor in determining how backward recall is performed. Beaudry, Saint-Aubin, Guérard, and Pâquet (2017) found that effects of word frequency and imageability were greatly reduced with spoken rather than manual recall.…”
Section: Discussionmentioning
confidence: 99%
“…An additional concern is that response modality may be a factor in determining how backward recall is performed. Beaudry, Saint-Aubin, Guérard, and Pâquet (2017) found that effects of word frequency and imageability were greatly reduced with spoken rather than manual recall.…”
Section: Discussionmentioning
confidence: 99%
“…In all but one experiment, Jalbert and her colleagues used an order reconstruction task in which participants responded by clicking on the items. Previous studies have shown that output modality can modulate the effects of key factors in short-term ordered recall (e.g., Beaudry, Saint-Aubin, Guérard & Pâquet, 2017;Harvey & Beaman, 2007). Furthermore, in the context of the word length effect, those procedural differences are very important.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with previous studies. In effect, although it is generally believed that recall performance is superior in forward than in backward recall, many studies showed no difference between both recall directions (e.g., Anderson, Bothell, Lebiere, & Matessa, 1998;Beaudry, Saint-Aubin, Guérard, & Pâquet, 2018;Bireta et al, 2010, Experiments 1-2;Farrand & Jones, 1996;Guérard, Saint-Aubin, Burns, & Chamberland, 2012;Guerrette et al, 2017;Li & Lewandowsky, 1995, Experiments 1-2;Madigan, 1971;Thomas, Milner, & Haberlandt, 2003).…”
Section: Discussionmentioning
confidence: 98%